Efeito do Genótipo sobre as Medidas Objetivas e Subjetivas da Carcaça de Cordeiros Terminados em Confinamento - Ramos De Siqueira, Edson [UNESP]; Fernandes, Simone [UNESP] (My University, 2000)
This experiment was carried out to compare the objective and subjective measurements of carcasses from 18 Corriedale and 18 Ile de France x Corriedale lambs, slaughtered at 30 to 32 kg LW. The lambs were weaned at 60 days of age, with 10 to 12 kg LW, finished in feedlot, and were full fed a diet with 15,0% CP and 70,0% TDN. After post-slaughter manipulation and cooled for 24 hours at 4°C, the objective and subjective carcass evaluations were made. There were differences between the studied genotype groups only for carcass external and internal length. The straightbreds lambs presented higher values for those measurements. However, by the overall mean observed for the longissimus dorsi area, the genotype groups presented the same amount of muscle in the carcass. The crossbred lamb carcass (IF x C) were considered to have the best conformation and presented the same subcutaneous fat cover of that of pour conformation. The studied genotype groups, in overall, were capable to meet two important demand of meat market requirements for lean carcass but with small subcutaneous fat cover to conserve the meat quality.
Effect of Objective and Subjective Measurements of Carcasses from Lambs Finished in Feedlot
Keywords: Carcass; Crossbreeding; Lamb; Lamb meat